The Influence of Service Quality and the Samsat Drive Thru System on Motor Vehicle Taxpayer Compliance with Tax Sanctions as Moderating Variables in Sidoarjo during the Covid-19 Pandemic: Pengaruh Kualitas Pelayanan dan Sistem Samsat Drive Thru Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Sanksi Perpajakan Sebagai Variabel Moderating di Sidoarjo pada Masa Pandemi Covid-19 - Putri, Selly Novindia; Dewi, Santi Rahma (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of service quality and the drive thru samsat system on motor vehicle taxpayer compliance, whether tax sanctions are able to moderate service quality and the drive thru samsat system on motor vehicle taxpayer compliance. This research method uses quantitative, data collection is done by distributing questionnaires. The population in this study were students of the 2018 accounting study program. The sampling technique used in this study was using the slovin formula as many as 155 respondents. The data analysis technique used is the PLS-SEM analysis technique with the SmartPLS V.3 program. The results of the study show that service quality has no significant effect on motor vehicle taxpayer compliance, the drive thru system has a significant effect on motor vehicle taxpayer compliance, tax sanctions are not able to moderate service quality on motor vehicle taxpayer compliance, tax sanctions are able to moderate the Samsat drive system. thru on motor vehicle tax compliance.